Evaluasi cara produksi pangan yang baik (CPPB) dan rekomendasi hazard analytical critical control point (HACCP) pada UKM teh sereh di Metro, Lampung - Ilham Marvie; Alexandra Trisna Putri (AGROINTEK, 2023)
Lemongrass (Cymbopogon citratus) is a plant often processed into brewing drinks such as tea. Small and Medium Enterprises (SMEs) Asha in Metro Lampung produces lemongrass tea with a production process consisting of size reduction, washing, drying, powdering, and packaging. To improve food safety in the production process is necessary to evaluate Good Manufacturing Practices/Good Food Production Methods (CPPB) and prepare recommendations for Hazard Analytical Critical Control Point (HACCP). The purpose of this study was to evaluate the application of the principles of CPPB and provide recommendations for the HACCP Plan to Asha SMEs. This research carries out by conducting field observations and interviews with several Asha SMEs stakeholders. The results showed that the CPPB evaluation had two serious discrepancy criteria and two critical discrepancy criteria. Therefore, Asha SMEs is included in the food home industry (IRTP) level 4 so that internal audit recommendations can carry out daily. The HACCP analysis results show three critical control points (CCP), namely soaking, drying and packaging. Critical and control limits are recommended by SNI 3836:2013 concerning packaged dry tea. The HACCP recommendation for Asha SMEs are to control the possibility of physical and coliform contamination during the repeated washing process with running water. Drying at 70oC for 12 hours helps reduce water activity in lemongrass tea in preventing mold growth. Furthermore, packaging with attention to the hygiene of workers and tools can prevent contamination of the final product of lemongrass tea